Trends and transformations within cultural journalism: a case study of newsmagazine Visão - Silva,Marisa Torres da (2014)
In the last ten years, the configuration of cultural journalism, regarding editorial and business models, has undergone profound changes. Nowadays, it cannot be separable from the context of cultural and creative industries, which requires a redefinition and expansion of the field, reinforcing its complexity, broadness and heterogeneity (Rivera, 2003). The emergence of more consumer-driven formats within journalism broadly speaking (Fürsich, 2012) is thus transforming cultural journalism into a continuum between culture, lifestyle and consumption (Kristensen, 2010), challenging existing definitions of cultural journalism as a distinct journalistic object (Kristensen & From, 2012). In this article, we intended to verify whether the identified trends are present in the Portuguese press media environment, using a newsmagazine (Visão) and its supplement (Visão Sete) as a case study. Combining quantitative (content analysis) and qualitative methodological approaches (interviews and discourse analysis), we stated that while Visão Sete is the clear example of the contemporary approach to culture as a service and a consumer good related to lifestyle, the culture section of the newsmagazine conveys a classic (and somewhat reductive) approach to culture, primarily related to artistic manifestations - which lead us to infer that nowadays newspapers and magazines are still looking for its position regarding cultural journalism.